Mixed carbon nanomaterial/epoxy resin for electrically conductive adhesives - Lopes, Paulo Estevão Caldeira (2020)
The increasing complexity of printed circuit boards (PCBs) due to miniaturization, increased the density of electronic components, and demanding thermal management during the assembly triggered the research of innovative solder pastes and electrically conductive adhesives (ECAs). Current commercial ECAs are typically based on epoxy matrices with a high load (>60%) of silver particles, generally in the form of microflakes. The present work reports the production of ECAs based on epoxy/carbon nanomaterials using carbon nanotubes (single and multi-walled) and exfoliated graphite, as well as hybrid compositions, within a range of concentrations. The composites were tested for morphology (dispersion of the conductive nanomaterials), electrical and thermal conductivity, rheological characteristics and deposition on a test PCB. Finally, the ECA’s shelf life was assessed by mixing all the components and conductive nanomaterials, and evaluating the cure of the resin before and after freezing for a time range up to nine months. The ECAs produced could be stored at −18 °C without affecting the cure reaction.